What has changed in the treatment of invasive candidiasis? A look at the past 10 years and ahead. (3rd January 2018) - Bassetti, Matteo; Righi, Elda; Montravers, Philippe; Cornely, Oliver A
Abstract: The treatment of invasive candidiasis has changed greatly in the past decade and must continue to evolve if we are to improve outcomes in this serious infection. A review of recent history may provide insights for the future. The morbidity and mortality of invasive candidiasis remain difficult to measure despite an obvious clinical burden. Current treatment guidelines now recommend echinocandins as first-line empirical treatment, with fluconazole as an acceptable alternative for selected patients, reflecting the efficacy demonstrated by echinocandins and increasing resistance observed with fluconazole. The selection of antifungal therapy now must consider not only resistance but also the shift in predominance from Candida albicans to non- albicans species, notably Candida glabrata . The recent emergence of Candida auris has been met with great interest, although the longer-term implications of this phenomenon remain unclear. The broad goal of treatment continues to be administration of safe, efficacious antifungal therapy as soon as possible. Diagnostic methods beyond traditional blood culture present an opportunity to shorten the time to an accurate diagnosis, and earlier treatment initiation based on prophylactic and empirical or pre-emptive strategies seeks to ensure timely therapeutic intervention. In addition, there are novel agents in the antifungal pipeline. These developments, as well as ongoing studies of dosing, toxicity and resistance development, are important items on the current research agenda and may play a role in future changes to the treatment of invasive candidiasis.